Poaching gangs and violence. The urban-rural divide in nineteenth-century Lancashire - Archer, John E. (The British journal of criminology, 1999)
Most historical research on poaching has focused on the southern and eastern counties of England, which were primarily rural and agrarian in character. This paper intends to examine poaching in the context of the urbanizing and industrializing environment of Lancashire. In so doing it will argue that a significant proportion of the poaching was undertaken by non-agrarian workers often from towns and cities who, in some cases, mixed poaching with other criminal pursuits. In other cases they were accused by the newly established police force of forming criminal gangs which posed a public danger. These features give northern poaching a distinctive character that suggests the poaching war was more brutal and bloody than in the more agricultural southern counties